Mastering Open Ed: Licensing, Accessibility, Creation, and Publishing OER - Brunet, Mélanie; Bonner, Tricia; Kehoe, Joanne; Roch, Shauna; Heck, Leo (Université d'Ottawa | University of Ottawa, 2023)
Mastering Open Ed, by eCampusOntario, is an essential guide for educators looking to adopt and create Open Educational Resources (OER). It provides insights into open licensing, sourcing quality OER, and using tools like Pressbooks and H5P to create engaging, accessible content. This Pressbook empowers educators to overcome financial barriers in education, contributing to a more accessible, equitable educational landscape.
Keywords: Open education; Open educational resources (OER); Accessibility; Open licensing; H5P; Pressbooks